2021
DOI: 10.3390/biology10070617
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Stroke after Spinal Anesthesia and Responses of Carotid or Cerebral Blood Flow and Baroreflex Functionality to Spinal Bupivacaine in Rats

Abstract: Spinal anesthesia is generally accepted as an effective and safe practice. Three rare incidents of postoperative cerebral infarction after surgery under spinal anesthesia prompted us to assess whether spinal bupivacaine may compromise carotid or cerebral blood flow. Postoperative examination after the stroke incident revealed that all three patients shared a common pathology of stenosis or atheromatosis in the carotid or middle cerebral artery. In a companion study using 69 Sprague-Dawley rats, subarachnoid ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Heart rate-guided phenylephrine after spinal anaesthesia 427 However, some studies have shown that spinal anaesthesia below T4 has no negative effect on baroreflex sensitivity, and the Bezold-Jarisch reflex, which may cause bradycardia, is uncommon. 16,17 In theory, blockade of the sympathetic nerve fibres would be several dermatomes above the level of loss of pinprick sensation, thus loss of pinprick sensation to T4 and above may block the cardiac sympathetic nerves. However, the block level does not reach T4 immediately after spinal injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart rate-guided phenylephrine after spinal anaesthesia 427 However, some studies have shown that spinal anaesthesia below T4 has no negative effect on baroreflex sensitivity, and the Bezold-Jarisch reflex, which may cause bradycardia, is uncommon. 16,17 In theory, blockade of the sympathetic nerve fibres would be several dermatomes above the level of loss of pinprick sensation, thus loss of pinprick sensation to T4 and above may block the cardiac sympathetic nerves. However, the block level does not reach T4 immediately after spinal injection.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between hypotension after spinal anaesthesia and pathological shock is that spinal anaesthesia may inhibit the cardiac sympathetic nerves and thus impair the baroreflex compensatory increase in HR. However, some studies have shown that spinal anaesthesia below T4 has no negative effect on baroreflex sensitivity, and the Bezold–Jarisch reflex, which may cause bradycardia, is uncommon 16,17 . In theory, blockade of the sympathetic nerve fibres would be several dermatomes above the level of loss of pinprick sensation, thus loss of pinprick sensation to T4 and above may block the cardiac sympathetic nerves.…”
Section: Discussionmentioning
confidence: 99%